Application of mass spectrometry for the detection of glycation and oxidation products in milk proteins - Meltretter, Jasmin; Pischetsrieder, Monika (Annals of the New York Academy of Sciences, 2008)
Protein mass spectometry techniques, such as electrospray ionization mass spectrometry or matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS), are effective methods to screen for protein modifications derived from the Maillard reaction. The analysis of the intact proteins reveals the major modification, most commonly the Amadori product, whereas partial enzymatic hydrolysis prior to mass spectrometry additionally allows the detection of minor adducts. Therefore, a mass spectrometric method was developed for the analysis of whey protein modifications occurring during heat treatment. The two main whey proteins, α-lactalbumin and β-lactoglobulin, were incubated with lactose in a milk model and modifications were recorded using MALDI-TOF-MS. The analysis of the intact proteins revealed protein species with 0-4 lactulosyl residues. Partial enzymatic hydrolysis with endoproteinase AspN prior to mass spectrometric analysis enabled the detection of further modifications and their localization in the amino acid sequence. Detected modifications were lactulosyllysine, N ε-(carboxymethyl)lysine, lysine aldehyde, methionine sulfoxide, cyclization of N-terminal glutamic acid to a pyrrolidone, and oxidation of cysteine or tryptophan. Protein modifications in heated milk and commercially available dairy products can be analyzed after the separation of the milk proteins using one-dimensional SDS-PAGE. © 2008 New York Academy of Sciences.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.applic
Keywords: α-lactalbumin; β-lactoglobulin; Advanced glycation end products; Maillard reaction; Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; Milk products; Oxidation